A kind of low friction high sand carrying linear adhesive and preparation method thereof

The low friction resistance high sand-carrying linear glue developed through supramolecular chemical self-assembly theory solves the problem of insufficient resistance reduction performance of linear glue in the existing technology, realizes high-efficiency fracturing of deep/ultra-deep oil and gas reservoirs, and provides key materials Support ensures the development of deep/ultra-deep oil and gas resources.

CN118955797BActive Publication Date: 2024-12-20SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411437861.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-20
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing water-based fracturing liquid linear glue has weak resistance reduction performance, resulting in unsatisfactory cracking and crack expansion and extension of deep and ultra-deep oil and gas reservoirs, making it difficult to reach the formation rupture pressure, resulting in fracturing failure, and for ground construction equipment and The pipe string proposes higher pressure levels, increasing sheathing risk and construction costs.

Method used

Using supramolecular chemical self-assembly theory and combined with the special requirements of the deep/ultra-deep oil and gas reservoir fracturing process, a low friction resistance high sand-carrying linear glue was developed, through acrylamide, sodium acrylate, and ionic hydrophobic monomers containing sulfonate , polymerization reaction of hydrophobic unit microblock regulator and molecular weight grader forms linear glue with high drag reduction and high sand carrying properties.

Benefits of technology

It significantly improves the shear degradation and sand carrying properties of linear adhesives, meets the fracturing fluid rheology and high drag reduction requirements of deep/ultra-deep oil and gas reservoirs, provides key material support, and ensures deep/ultra-deep oil and gas resources. efficient development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955797B_ABST
    Figure CN118955797B_ABST
Patent Text Reader

Abstract

The invention discloses a low-friction high-sand-carrying linear adhesive and a preparation method thereof, and belongs to the field of deep well / extra-deep well volume fracturing. The linear adhesive is prepared by polymerization reaction of acrylamide, sodium acrylate, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight grading agent and a composite initiator. Through the special sulfonate ion-containing hydrophobic monomer, the hydrophobic unit microblock regulator matched with the hydrophobic monomer and the control of molecular weight, the polymer solubility and viscosity-increasing performance can be significantly improved; the shear resistance of the linear adhesive is improved; the linear adhesive has excellent sand-carrying performance and drag-reducing performance; the shortcomings of the existing linear adhesive such as weak shear resistance, fast drag-reduction rate drop, and poor sand-carrying performance can be overcome, and the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction" can be met, so as to provide key material support for the development of deep / ultra-deep oil and gas resources and ensure the goal of efficient development of deep / ultra-deep oil and gas resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of deep well / ultra-deep well volume fracturing, and in particular to a low-friction high-sand-carrying linear adhesive and a preparation method thereof. Background Art

[0002] Existing water-based fracturing fluid linear glue (20-50cP) is mainly linear high molecular weight polyacrylamide, which has the characteristics of weak drag reduction performance, greatly reduces the net pressure at the bottom of the well and in the fracture, which may lead to unsatisfactory crack opening, crack expansion and extension, encounter difficult-to-press formations, and even difficult to reach the formation fracture pressure, resulting in fracturing failure. The deeper the well and the longer the horizontal section, the more prominent the contradiction. In this case, high surface pump pressure is often required to overcome friction to obtain sufficient bottom hole pressure and net pressure in the fracture to reach and exceed the formation fracture pressure and fracture expansion extension pressure, which requires higher pressure level requirements for ground construction equipment and pipe strings, and at the same time leads to problems such as increased risk of casing change and greatly increased construction costs. It is difficult to meet the "high wellbore drag reduction" requirements for fracturing deep / ultra-deep oil and gas reservoirs. This technical bottleneck has become a significant obstacle to the development of deep and ultra-deep oil and gas resources. Therefore, the development of slippery water linear glue with shear resistance and high drag reduction has become a technical problem that needs to be broken through. This patent applies the supramolecular chemical self-assembly theory and combines the special requirements of the pressure fluid rheology in the fracturing process of deep / ultra-deep oil and gas reservoirs to develop a linear gel fracturing fluid with high drag reduction and high sand carrying capacity. This invention is expected to provide key material support for the development of deep / ultra-deep oil and gas resources, solve the technical problems of fracturing development of deep / ultra-deep oil and gas reservoirs, and ensure the efficient development of deep / ultra-deep oil and gas resources. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a low-friction high-sand-carrying linear adhesive and a preparation method thereof. The linear adhesive is prepared by polymerization reaction of acrylamide, sodium acrylate, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator. The present invention can significantly improve the polymer solubility and viscosity-increasing properties through the control of special sulfonate ion-containing hydrophobic monomers, hydrophobic unit microblock regulators matched with the hydrophobic monomers and polymer molecular weight; improve the shear degradation resistance of the linear adhesive; have excellent sand-carrying performance and drag reduction performance; overcome the shortcomings of the existing linear adhesive such as weak shear resistance, fast drag reduction rate drop, and poor sand-carrying performance, and can meet the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction". The invention provides key material support for the development of deep / ultra-deep oil and gas resources and ensures the goal of efficient development of deep / ultra-deep oil and gas resources.

[0004] In order to achieve the above technical effects, the following technical solutions are adopted:

[0005] A low-friction high-sand-carrying linear adhesive, which is formed by the polymerization reaction of acrylamide, a hydrophobic monomer containing sulfonate ions, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator, and then hydrolyzed, i.e., a post-hydrolysis process; or formed by the polymerization reaction of acrylamide, sodium acrylate, a hydrophobic monomer containing sulfonate ions, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator, i.e., a copolymerization process;

[0006] The molecular structure of the linear glue is:

[0007] ;

[0008] Wherein, x, y, z are the number of each repeating unit;

[0009] In the post-hydrolysis process, the molar ratio of acrylamide to the sulfonate ion-containing hydrophobic monomer is 1: 0.005-0.01;

[0010] In the copolymerization process, the molar ratio of acrylamide, sodium acrylate, and sulfonate-containing ion-type hydrophobic monomer is 1: 0.2-0.4: 0.005-0.01;

[0011] The mass ratio of the hydrophobic unit microblock regulator to the sulfonate ion-containing hydrophobic monomer is 2:1 to 1:1;

[0012] The mass ratio of molecular weight modifier to reaction system is 0.015%-0.025%;

[0013] The mass ratio of the composite initiator to the reaction system is 0.0115%-0.0225%;

[0014] After the polymerization reaction is completed in the post-hydrolysis process, sodium hydroxide is used for post-hydrolysis, and the molar ratio of acrylamide monomer to sodium hydroxide is 1:0.2-0.4;

[0015] The structural formula of the sulfonate ion-containing hydrophobic monomer is:

[0016] ;

[0017] Wherein, the R group is a C14 alkyl group or a C16 alkyl group;

[0018] The hydrophobic unit microblock regulator is one or more of AEO-7, AEO-9, OP-8, and OP-10;

[0019] The molecular weight regulator is one or more of sodium formate, sodium hypophosphite, and n-butyl mercaptan;

[0020] The composite initiator is a multi-element initiator, which is composed of an inorganic oxidant, an organic oxidant, a reducing agent, and a water-soluble azo initiator. The inorganic oxidant is a persulfate, and the addition amount is 0.002-0.004% of the reaction system; the organic oxidant is an organic hydrogen peroxide, and the addition amount is 0.001-0.003% of the reaction system; the reducing agent is a sulfite and a bisulfite, and the addition amount is 0.0075-0.0125% of the reaction system; the addition amount of the water-soluble azo initiator is 0.001-0.003% of the reaction system.

[0021] Furthermore, the molecular weight of the linear rubber is in the range of 15-20 million.

[0022] Furthermore, the inorganic oxidant is ammonium persulfate, sodium persulfate, potassium persulfate, or hydrogen peroxide; and the organic oxidant is one or more of tert-butyl hydroperoxide and cumene hydroperoxide.

[0023] Furthermore, the reducing agent is one of sodium sulfite, sodium bisulfite and sodium metabisulfite.

[0024] Furthermore, the water-soluble azo initiator is one of 2,2-azo(2-(2-imidazolin-2-yl)propane) dihydrochloride, 2,2-azo(2-methyl-N-(2-hydroxyethyl)acrylamide), and 2,2-azobis(2-methylpropane) hydrochloride.

[0025] Furthermore, the composite initiator is tert-butyl hydroperoxide, ammonium persulfate, sodium bisulfite, and 2,2-azo(2-(2-imidazoline-2-yl)propane) dihydrochloride.

[0026] Furthermore, the preparation method of the sulfonate ion-containing hydrophobic monomer is:

[0027] Step S1: in a three-necked flask equipped with a magnetic stirrer, a reflux cold flow tube, a thermometer, and two constant pressure dropping funnels, tetradecylamine or hexadecylamine and a catalyst are added in sequence, 2-sodium bromoethylsulfonate or 2-sodium chloroethylsulfonate solution is added to one of the constant pressure dropping funnels, and NaOH solution is added to the other constant pressure dropping funnel; by adjusting the dropping speed of the NaOH solution, the pH value of the reaction is controlled, and the reaction is carried out at a temperature of 50-70° C. for 6-9 hours; after the reaction is completed, a precipitate is precipitated in ethanol, and filtered to obtain an intermediate sodium 2-tetradecylaminoethanesulfonate or sodium 2-hexadecylaminoethanesulfonate;

[0028] Step S2: dissolving the intermediate obtained in step S1 in dichloromethane, and adding Na2CO3 as an acid binding agent; dropping acryloyl chloride from a constant pressure dropping funnel, controlling the temperature at 15-20°C, reacting for 18-24 hours, removing dichloromethane by reduced pressure distillation, and then recrystallizing with ethanol to obtain the target monomer, which is a sulfonate ion-containing hydrophobic monomer.

[0029] Furthermore, in the step S1, the molar ratio of tetradecylamine or hexadecylamine to sodium 2-bromoethylsulfonate or sodium 2-chloroethylsulfonate is 1:0.8-1:0.9; the catalyst is tetrabutylammonium bromide, and its content is 1% of the mass of tetradecylamine or hexadecylamine; during the reaction, the dropping speed of the NaOH solution is adjusted according to the pH change to control the pH value at 9-12; in the step S2, the molar ratio of the intermediate, Na2CO3, and acryloyl chloride is 1:3:3.

[0030] A method for preparing a low-friction high-sand-carrying linear adhesive using a post-hydrolysis process or a copolymerization process:

[0031] Among them, the post-hydrolysis process is detailed as follows:

[0032] The acrylamide monomer and the sulfonate ion-containing hydrophobic monomer are added according to the formula ratio, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 20-35%; the hydrophobic unit microblock regulator and the molecular weight regulator are added to the mixed solution, and then the pH value of the solution is adjusted to 7.0-9.0, and the system temperature is lowered to 0-5°C and then a water-soluble azo initiator and a reducing agent are added; nitrogen is introduced and stirred for 30-40 minutes, and then an oxidant is added, and adiabatic polymerization is carried out for 3-8 hours. After the adiabatic polymerization is completed, granulation, hydrolysis, drying, and crushing are carried out to obtain a target polymer.

[0033] The copolymerization process is detailed as follows:

[0034] The acrylamide monomer, sodium acrylate and sulfonate ion-containing hydrophobic monomer are added according to the formula ratio, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 20-35%; after adjusting the pH to 7.0 with sodium hydroxide, a hydrophobic unit microblock regulator and a molecular weight regulator are added to the mixed solution, and then the pH value of the solution is adjusted to 7.0-9.0, and a water-soluble azo initiator and a reducing agent are added after the system temperature is reduced to 0-5°C; nitrogen is introduced and stirred for 30-40 minutes, and then an oxidant is added, and adiabatic polymerization is carried out for 3-8 hours. After the adiabatic polymerization is completed, granulation, drying and crushing are carried out to obtain a target polymer.

[0035] Furthermore, the pH value of the solution is adjusted by sodium hydroxide and acetic acid; after the addition of the hydrophobic unit microblock regulator, the pH value of the solution is 8.0-8.5; the system temperature is 0° C.; and the thermal insulation polymer time is 5-7 hours.

[0036] The invention discloses a low-friction high-sand-carrying linear adhesive and a preparation method thereof. The linear adhesive is prepared by polymerization reaction of acrylamide, sodium acrylate, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator. The invention cooperates with each other through special sulfonate ion-containing hydrophobic monomers, a hydrophobic unit microblock regulator matched with the hydrophobic monomer and the control of polymer molecular weight, and synergistic polymerization is achieved. Several polymer substances act together to synthesize a polymer molecular structure that is different from the prior art. The difference in molecular structure and the superiority of the molecular structure can significantly improve the polymer solubility and viscosity-increasing performance; improve the shear degradation resistance of the linear adhesive; have excellent sand-carrying performance and drag reduction performance; overcome the shortcomings of the existing linear adhesive such as weak shear resistance, fast decrease in drag reduction rate and poor sand-carrying performance, and can meet the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction". The invention provides key material support for the development of deep / ultra-deep oil and gas resources and ensures the goal of efficient development of deep / ultra-deep oil and gas resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0038] Figure 1 is the H of the sulfonate ion type hydrophobic monomer in the embodiment of the present invention. 1 - NMR spectra;

[0039] Figure 2 It is the HPLC-MS chart of the sulfonate ion type hydrophobic monomer in the embodiment of the present invention. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0043] First, a sulfonate ion-containing hydrophobic monomer is synthesized, and the preparation method thereof is as follows:

[0044] Step S1: In a three-necked flask equipped with a magnetic stirrer, a reflux cold flow tube, a thermometer, and two constant pressure dropping funnels, tetradecylamine or hexadecylamine and a catalyst (tetrabutylammonium bromide) are added in sequence, 2-bromoethyl sodium sulfonate or 2-chloroethyl sodium sulfonate solution is added to one of the constant pressure funnels, and NaOH solution is added to the other constant pressure dropping funnel; the pH value of the reaction is controlled by adjusting the dropping speed of the NaOH solution, and the reaction is carried out at a temperature of 50-70° C. for 6-9 hours; after the reaction is completed, a precipitate is precipitated in ethanol, and filtered to obtain an intermediate sodium 2-tetradecylaminoethanesulfonate or sodium 2-hexadecylaminoethanesulfonate;

[0045] In the step S1, the molar ratio of tetradecylamine or hexadecylamine to sodium 2-bromoethylsulfonate or sodium 2-chloroethylsulfonate solution is 1:0.8-1:0.9; the catalyst is tetrabutylammonium bromide, and its content is 1% of the mass of tetradecylamine or hexadecylamine; and the pH value is controlled between 9 and 12 by controlling the dripping speed of the sodium hydroxide solution.

[0046] Step S2: dissolving the intermediate obtained in step S1 in dichloromethane, and adding Na2CO3 as an acid binding agent; dropping acryloyl chloride from a constant pressure dropping funnel, controlling the temperature at 20°C, reacting for 18 hours, removing dichloromethane by reduced pressure distillation, and then recrystallizing with ethanol to obtain the target monomer, which is a sulfonate ion-containing hydrophobic monomer (R group is a C16 or C14 alkyl group); in step S2, the molar ratio of the intermediate, Na2CO3, and acryloyl chloride is 1:3:3.

[0047] The obtained H containing sulfonate ion type hydrophobic monomer (R group is C14 alkyl) 1 -NMR images Figure 1 As shown; the HPLC-MS diagram of the hydrophobic monomer containing sulfonate ion (R group is C14 alkyl) is as follows Figure 2 shown.

[0048] Example 1

[0049] Acrylamide monomer, sodium acrylate monomer, and sulfonate ion-containing hydrophobic monomer (R group is C16 alkyl) are added in a ratio of 1:0.3:0.0075, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 25%; a hydrophobic unit microblock regulator AEO-7 is added to the mixed solution in an amount such that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer is 1.5:1, and 200 ppm of sodium formate, a molecular weight regulator, is added, and then the pH value of the solution is adjusted to 8.0 using sodium hydroxide and acetic acid. After the system temperature is adjusted to 0°C, 100 ppm of sodium bisulfite, 30 ppm of ammonium persulfate, and 10 ppm of azo initiator 2,2-azo (2- (2-imidazoline-2-yl) propane) dihydrochloride are added, nitrogen is introduced and stirred for 30 minutes, and then 20 ppm of tert-butyl hydroperoxide is added, and adiabatic polymerization is carried out for 3-8 hours. After the adiabatic polymerization is completed, granulation, drying, and crushing are performed to obtain the target polymer. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 1 was measured and calculated using an Ubbelohde viscometer (0.55 mm tube diameter) according to GB / T 12005.10-92 and was found to be 17 million.

[0050] Example 2

[0051] The method of Example 1 was followed, except that acrylamide monomer, sodium acrylate monomer, and sulfonate ion-containing hydrophobic monomer were added in a ratio of 1:0.2:0.0075. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 2 was 17.1 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T12005.10-92.

[0052] Example 3

[0053] The method of Example 1 was followed, except that acrylamide monomer, sodium acrylate monomer, and sulfonate ion-containing hydrophobic monomer were added in a ratio of 1:0.4:0.0075. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 3 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T12005.10-92, and was 17.6 million.

[0054] Example 4

[0055] The method of Example 1 was followed, except that acrylamide monomer, sodium acrylate monomer, and sulfonate ion-containing hydrophobic monomer were added in a ratio of 1:0.3:0.005. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 4 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T12005.10-92, and was 17.3 million.

[0056] Example 5

[0057] The method of Example 1 was followed, except that acrylamide monomer, sodium acrylate monomer, and sulfonate ion-containing hydrophobic monomer were added in a ratio of 1:0.3:0.01. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 5 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T12005.10-92, and was 17.5 million.

[0058] Example 6

[0059] The method of Example 1 was followed, except that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer was 2: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 6 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 17.1 million.

[0060] Example 7

[0061] The method of Example 1 was followed, except that the mass ratio of the hydrophobic unit microblock regulator to the hydrophobic monomer was 1: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 7 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 17.2 million.

[0062] Example 8

[0063] The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with OP-8. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 8 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 17.4 million.

[0064] Example 9

[0065] The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with OP-10. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 9 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and the result was 18.1 million.

[0066] Example 10

[0067] The method of Example 1 was followed, except that the hydrophobic unit microblock regulator was replaced with AEO-9. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 10 was measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92, and was 17.5 million.

[0068] Embodiment 11

[0069] The acrylamide monomer and the sulfonate ion-containing hydrophobic monomer (R group is a C16 alkyl) are added in a ratio of 1:0.0075, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 25%; the hydrophobic unit microblock regulator AEO-7 is added to the mixed solution, and the added amount is a hydrophobic unit microblock regulator and a sulfonate ion-containing hydrophobic monomer mass ratio of 1.5:1, and 200ppm of sodium formate, a molecular weight regulator, is added, and then sodium hydroxide and acetic acid are used to adjust the solution pH to 8 .0, adjust the system temperature to 0°C, add 100ppm of sodium bisulfite, 30ppm of ammonium persulfate, 10ppm of azo initiator 2,2-azo (2- (2-imidazoline-2-yl) propane) dihydrochloride, introduce nitrogen and stir for 30 minutes, then add 20ppm of tert-butyl hydroperoxide, and perform adiabatic polymerization for 3-8h. After the adiabatic polymerization is completed, granulate, hydrolyze (add sodium hydroxide with a molar mass of 30% of acrylamide, and seal and hydrolyze at 90°C for 2 hours), dry, and crush to obtain the target polymer. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Example 11 was tested and calculated according to GB / T 12005.10-92 using an Ubbelohde viscometer (0.55mm diameter) to be 17.6 million.

[0070] Comparative Example 1

[0071] The method of Example 1 was followed, except that the R group of the sulfonate ion hydrophobic monomer was a C12 alkyl group. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 1 was 17.1 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0072] Comparative Example 2

[0073] The method of Example 1 was followed, except that the R group of the sulfonate ion hydrophobic monomer was a C18 alkyl group. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 2 was 17.2 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0074] Comparative Example 3

[0075] The method of Example 1 was followed, except that the hydrophobic monomer was dimethyl hexadecyl allyl ammonium chloride. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 3 was 17.4 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0076] Comparative Example 4

[0077] The method of Example 1 was followed, except that the mass ratio of the microblock regulator to the hydrophobic monomer was 3: 1. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 4 was 17.3 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0078] Comparative Example 5

[0079] The method of Example 1 was followed, except that the mass ratio of the microblock regulator to the hydrophobic monomer was 1:2. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 5 was 17.5 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0080] Comparative Example 6

[0081] The method of Example 1 was followed, except that the amount of the molecular weight modifier sodium formate was increased to 300 ppm. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 6 was tested and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92 to be 12 million.

[0082] Comparative Example 7

[0083] The method of Example 1 was followed, except that the amount of sodium formate added as a molecular weight regulator was reduced to 100 ppm. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 7 was tested and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92 and was 22 million.

[0084] Comparative Example 8

[0085] The method of Example 1 was followed, except that the microblock regulator was replaced with AEO-5. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 8 was 17.5 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0086] Comparative Example 9

[0087] The method of Example 1 was followed, except that the microblock regulator was replaced with OP-7. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 9 was 17.1 million, as measured by an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0088] Comparative Example 10

[0089] The method of Example 1 was followed, except that the microblock regulator was replaced with OP-13. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 10 was 17.3 million, as measured by an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0090] Comparative Example 11

[0091] The method of Example 1 was followed, except that no block grader was added. The viscosity average molecular weight of the high temperature resistant and salt resistant instant fracturing fluid thickener obtained in Comparative Example 11 was 17.2 million, as measured and calculated using an Ubbelohde viscometer (0.55 mm diameter) according to GB / T 12005.10-92.

[0092] Comparative Example 12

[0093] The method of Example 1 was followed, except that no azo component was added to the initiator. The reaction failed, the colloid was very soft, and a large amount of unpolymerized liquid was present.

[0094] Comparative Example 13

[0095] The method of Example 1 was followed, except that ammonium persulfate was not added to the initiator. The reaction failed, the temperature was not raised further after reaching 20°C, a large amount of monomers were not polymerized, and the reaction failed.

[0096] Comparative Example 14

[0097] The method of Example 1 was followed, except that tert-butyl hydroperoxide was not added to the initiator. The reaction could not be initiated and the polymerization failed.

[0098] Comparative Example 15

[0099] The mainstream high molecular weight linear adhesive on the market is partially hydrolyzed polyacrylamide, with a molecular weight of 30 million and a hydrolysis degree of 30%.

[0100] The polymer solution performance evaluation method is as follows:

[0101] (1) Viscosity enhancement performance

[0102] Stir in clean water at 25°C and 500 r / min for 3 min and measure with a six-speed viscometer for 170 s -1 Under this condition, the viscosity of the concentration is divided into 600ppm to 3000pmm, and the concentration corresponding to 20mPa·s and 50mPa·s is found, as shown in Table 1.

[0103] Table 1 Concentrations corresponding to sample viscosities of 20 mPa·s and 50 mPa·s

[0104]

[0105] The comparative polymers that failed to meet the criteria in the tackifying test were not evaluated for other properties.

[0106] (2) Drag reduction performance

[0107] The drag reduction rates of the test examples and comparative examples were measured in accordance with the provisions of Chapter 7.8 of SY-T 7627-2021 for determining the drag reduction rate, and the 5-min drag reduction rate data was taken as the drag reduction rate value, as shown in Table 2.

[0108] Table 2 Drag reduction rate corresponding to sample viscosity of 20mPa·s and 50mPa·s

[0109]

[0110] (3) Sand carrying performance

[0111] Take 1000 mL of the target solution and prepare about 400 mL. Stir at 500 r / min for 3 min during sample preparation. Pour 100 mL of the test solution into a 100 mL measuring cylinder, and then test the sedimentation rate of 20 / 40 mesh ceramsite in the measuring cylinder. Repeat the test of the sedimentation rate of 20 ceramsite particles, and then take the average value, as shown in Table 3.

[0112] Table 3 Sedimentation velocity corresponding to sample viscosity of 30 mPa·s

[0113]

[0114] (4) Shear resistance

[0115] The sample was loaded into the Hake RS6000 high temperature and high pressure rheometer, and the rotor model was PZ36. The test temperature was set to 30°C and the sample was subjected to a shear rate of 100 s -1 Shear for 30 min under the conditions, record the viscosity value μ1, and increase the shear rate to 511s -1 , shear for 15 min, and then increase the shear rate to 750 s -1 , shearing for 15 min, and finally the shearing rate was reduced to 100 s -1 , shear for 30 minutes and record the viscosity value μ2.

[0116] The shear viscosity recovery rate is shown in formula 1:

[0117] w = μ2 / μ1 (Formula 1)

[0118] Table 4 Shear properties corresponding to viscosities of 20 mPa·s and 50 mPa·s

[0119]

[0120] In summary, the present invention discloses a low-friction high-sand-carrying linear adhesive and a preparation method thereof. The linear adhesive is formed by polymerization reaction of acrylamide, sodium acrylate, a sulfonate ion-containing hydrophobic monomer, a hydrophobic unit microblock regulator, a molecular weight regulator and a composite initiator. The present invention cooperates with each other through special sulfonate ion-containing hydrophobic monomers, a hydrophobic unit microblock regulator matched with the hydrophobic monomer, and the control of polymer molecular weight, and synergistic polymerization. Several polymer substances work together to synthesize a polymer molecular structure that is different from the prior art. The difference in molecular structure and the excellence of the molecular structure can significantly improve the polymer solubility and viscosity-increasing performance; improve the shear degradation resistance of the linear adhesive; have excellent sand-carrying performance and drag reduction performance; overcome the shortcomings of the existing linear adhesive such as weak shear resistance, fast decrease in drag reduction rate, and poor sand-carrying performance, and can meet the special requirements of deep / ultra-deep oil and gas reservoir fracturing on fracturing fluid rheology and "high wellbore drag reduction". The invention provides key material support for the development of deep / ultra-deep oil and gas resources and ensures the goal of efficient development of deep / ultra-deep oil and gas resources.

[0121] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A low friction and high sand carrying linear adhesive, It is characterized in that The linear glue is formed by hydrolysis after polymerization reaction of acrylamide, acrylic acid, hydrophobic monomer containing sulfonate ions, hydrophobic unit microblock regulator, molecular weight regulator and composite initiator, i.e. post-hydrolysis process; or formed by polymerization reaction of acrylamide, sodium acrylate, hydrophobic monomer containing sulfonate ions, hydrophobic unit microblock regulator, molecular weight regulator and composite initiator, i.e. copolymerization process; The molecular structure of the linear glue is: ; Wherein, x, y, z are the number of each repeating unit; In the post-hydrolysis process, the molar ratio of acrylamide to the sulfonate ion-containing hydrophobic monomer is 1: 0.005-0.01; In the copolymerization process, the molar ratio of acrylamide, sodium acrylate, and sulfonate-containing ion-type hydrophobic monomer is 1: 0.2-0.4: 0.005-0.01; The mass ratio of the hydrophobic unit microblock regulator to the sulfonate ion-containing hydrophobic monomer is 2:1 to 1:1; The mass ratio of molecular weight modifier to reaction system is 0.015%-0.025%; The mass ratio of the composite initiator to the reaction system is 0.0115%-0.0225%; After the polymerization reaction is completed in the post-hydrolysis process, sodium hydroxide is used for post-hydrolysis, and the molar ratio of acrylamide monomer to sodium hydroxide is 1:0.2-0.4; The structural formula of the sulfonate ion-containing hydrophobic monomer is: ; Wherein, the R group is a C14 alkyl group or a C16 alkyl group; The hydrophobic unit microblock regulator is one or more of AEO-7, AEO-9, OP-8, and OP-10; The molecular weight regulator is one or more of sodium formate, sodium hypophosphite, and n-butyl mercaptan; The composite initiator is a multi-element initiator, which is composed of an inorganic oxidant, an organic oxidant, a reducing agent, and a water-soluble azo initiator. The inorganic oxidant is a persulfate, and the addition amount is 0.002-0.004% of the reaction system; the organic oxidant is an organic hydrogen peroxide, and the addition amount is 0.001-0.003% of the reaction system; the reducing agent is a sulfite or a bisulfite, and the addition amount is 0.0075-0.0125% of the reaction system; the addition amount of the water-soluble azo initiator is 0.001-0.003% of the reaction system.

2. A low friction high sand carrying linear adhesive as claimed in claim 1, It is characterized in that The molecular weight of the linear gel is in the range of 15-20 million.

3. A low friction high sand carrying linear adhesive as claimed in claim 1, It is characterized in that The inorganic oxidant is one or more of ammonium persulfate, sodium persulfate, and potassium persulfate; the organic oxidant is one or more of tert-butyl hydroperoxide and isopropylbenzene hydroperoxide.

4. A low friction high sand carrying linear adhesive as claimed in claim 1, It is characterized in that The reducing agent is one of sodium sulfite, sodium bisulfite and sodium metabisulfite.

5. A low friction high sand carrying linear adhesive as claimed in claim 1, It is characterized in that The water-soluble azo initiator is one of 2,2-azo(2-(2-imidazoline-2-yl)propane) dihydrochloride, 2,2-azo(2-methyl-N-(2-hydroxyethyl)acrylamide), and 2,2-azobis(2-methylpropane) hydrochloride.

6. A low friction high sand carrying linear adhesive as claimed in claim 1, It is characterized in that The composite initiator is tert-butyl hydroperoxide, ammonium persulfate, sodium bisulfite, and 2,2-azo(2-(2-imidazoline-2-yl)propane) dihydrochloride.

7. A low friction high sand carrying linear adhesive as claimed in claim 1, It is characterized in that The preparation method of the sulfonate ion-containing hydrophobic monomer is as follows: Step S1: in a three-necked flask equipped with a magnetic stirrer, a reflux cold flow tube, a thermometer, and two constant pressure dropping funnels, tetradecylamine or hexadecylamine and a catalyst are added in sequence, 2-sodium bromoethylsulfonate or 2-sodium chloroethylsulfonate solution is added to one of the constant pressure dropping funnels, and NaOH solution is added to the other constant pressure dropping funnel; by adjusting the dropping speed of the NaOH solution, the pH value of the reaction is controlled, and the reaction is carried out at a temperature of 50-70° C. for 6-9 hours; after the reaction is completed, a precipitate is precipitated in ethanol, and filtered to obtain an intermediate sodium 2-tetradecylaminoethanesulfonate or sodium 2-hexadecylaminoethanesulfonate; Step S2: The intermediate prepared in step S1 is dissolved in dichloromethane and Na 2 CO 3 as an acid-binding agent; acryloyl chloride is added dropwise from a constant pressure dropping funnel, the temperature is controlled at 15-20°C, and after reacting for 18-24 hours, dichloromethane is removed by reduced pressure distillation, and then recrystallization is performed using ethanol to obtain the target monomer, which is a sulfonate ion-containing hydrophobic monomer.

8. A low friction high sand carrying linear adhesive as claimed in claim 7, It is characterized in that In the step S1, the molar ratio of tetradecylamine or hexadecylamine to sodium 2-bromoethylsulfonate or sodium 2-chloroethylsulfonate is 1:0.8-1:0.9; the catalyst is tetrabutylammonium bromide, and its content is 1% of the mass of tetradecylamine or hexadecylamine; during the reaction, the dropping speed of the NaOH solution is adjusted according to the pH change to control the pH value at 9-12; in the step S2, the intermediate, Na 2 CO 3 , the molar ratio of acryloyl chloride is 1:3:

3.

9. A method for preparing a low-friction high-sand-carrying linear adhesive as claimed in any one of claims 1 to 8, It is characterized in that The preparation method uses a post-hydrolysis process or a copolymerization process: Among them, the post-hydrolysis process is detailed as follows: Adding acrylamide monomer, acrylic acid, and sulfonate ion-containing hydrophobic monomer according to the formula ratio, and using ultrapure water to prepare a mixed solution with a total monomer mass concentration of 20-35%; adding a hydrophobic unit microblock regulator and a molecular weight regulator to the mixed solution, and then adjusting the solution pH to 7.0-9.0, and adding a water-soluble azo initiator and a reducing agent after lowering the system temperature to 0-5°C; introducing nitrogen and stirring for 30-40 minutes, and then adding an oxidant, and adiabatic polymerization for 3-8 hours. After the adiabatic polymerization is completed, granulation, hydrolysis, drying, and crushing are performed to obtain a target polymer; The copolymerization process is detailed as follows: The acrylamide monomer, sodium acrylate and sulfonate ion-containing hydrophobic monomer are added according to the formula ratio, and ultrapure water is used to prepare a mixed solution with a total monomer mass concentration of 20-35%; after adjusting the pH to 7.0 with sodium hydroxide, a hydrophobic unit microblock regulator and a molecular weight regulator are added to the mixed solution, and then the pH value of the solution is adjusted to 7.0-9.0, and a water-soluble azo initiator and a reducing agent are added after the system temperature is reduced to 0-5°C; nitrogen is introduced and stirred for 30-40 minutes, and then an oxidant is added, and adiabatic polymerization is carried out for 3-8 hours. After the adiabatic polymerization is completed, granulation, drying and crushing are carried out to obtain a target polymer.

10. The preparation method as claimed in claim 9, It is characterized in that The pH value of the solution is adjusted by sodium hydroxide and acetic acid; after the hydrophobic unit microblock regulator is added, the pH value of the solution is 8.0-8.5; the system temperature is 0° C.; and the adiabatic polymerization time is 5-7 hours.